PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PEMBERIAN BANTUAN BIBIT CENGKIH DAN BIBIT IKAN AIR TAWAR DI DESA MODAYAG TIMUR KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - LUBYS, MIRNANDA APRILIA AMIR; RARES, JOYCE; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2021)
Village community empowerment is carried out to develop independence and improve community welfareby increasing skills and abilities in managing and utilizing existing resources in the village. The purposeof this empowerment is to improve the development of resources, improve the way of managingresources, and also to improve the lives of the local community so that they can be even better. Therefore,this research was conducted to answer questions about community empowerment through the assistanceprogram for clove seeds and freshwater fish seeds in east modayag village, modayag district, east bolaangmongondow regency. This study uses a qualitative descriptive research design because in this study,researchers as much as possible try to be able to solve existing problems by conducting interviews with 8informants and also by collecting documents related to community empowerment. The results of this studyare explaining about community empowerment in the village of east modayag that has not gone well andhas not been in accordance with the desired goals.Keywords : empowerment, program, assistance